Evaluasi Mutu Protein Tepung Tempe dan Tepung Kedelai Rebus pada Tikus Percobaan - Made Astawan; Tutik Wresdiyati; Armando M Saragih (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2015)
Soybean is a strategic commodity in Indonesia and it is the main raw material for food processing such as tempe, tofu,and soy sauce. Tempe is a traditional food that has been known in Indonesia, which is made by fermentation process using Rhizopus sp. The main weakness of fresh tempe is the short shelf- life at room temperature, only last two days. Processing tempe into tempe our is one of efforts to extend the shelf life. This research aimes to evaluate protein nutritional quality of tempe our and soybean our, compared to casein as a standard by using rats as animal model. Weight gain of each group of rats was increased during 28 days of experiment. The protein nutritional quality of tempe our was signi cantly higher (p<0.05) than that of boiled soy our in the value of feed convertion efficiency and true protein digestibility; highly significantly higher (p<0.01) in the value of protein efficiency ratio and net protein ratio; and not significantly different (p>0.05) in the value of biological value and net protein utulization. From the results of protein nutritional quality evaluation, it could be concluded that tempe our had better nutritional quality than boliled soy our, and even better than casein.